2015
DOI: 10.18006/2015.3(2).207.212
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and organoleptic evaluation of cowpea (Vignaugu culata) and soybean (Glycine max) blends for the production of Moi-moi and Ekuru (steamed cowpea paste)

Abstract: Present study was aimed to investigate the utilization of cowpea in combination with soybean for the production of steamed cowpea paste Moi-Moi and Ekuru. For these preparations cowpea used in different ration for the substitution of soybean. The samples were processed into paste using traditional method the pasted samples were subjected to proximate analysis and two difference local products produced (Moi-moi and Ekuru) were subjected to sensory evaluation. The results of proximate analysis showed that the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
3
1
Order By: Relevance
“…It also works in synergy with minerals to enhance growth, provide energy, repair, and regulate body processes (Okwunodulu., Peter, & Okwunodulu, 2019). Protein content obtained from this study compares well with the study of Ogundele et al (2015) who reported protein content of 4.40-11.60% for moi-moi made from cowpea and soybean flour blends. It is also close to the study of Agbara et al…”
Section: Proximate Compositionsupporting
confidence: 87%
See 2 more Smart Citations
“…It also works in synergy with minerals to enhance growth, provide energy, repair, and regulate body processes (Okwunodulu., Peter, & Okwunodulu, 2019). Protein content obtained from this study compares well with the study of Ogundele et al (2015) who reported protein content of 4.40-11.60% for moi-moi made from cowpea and soybean flour blends. It is also close to the study of Agbara et al…”
Section: Proximate Compositionsupporting
confidence: 87%
“…Moisture content of moi-moi obtained from this study is lower when compared with 52.06-55.06% for moi-moi made from cowpea-Asparagus bean flours (Nwosu, 2011). It is also lower than that reported by Ogundele, Ojubanire, and Bamidele (2015) for cowpea/soybean moi-moi (48.36-53.93%). The moisture content of moi-moi from this study is within the range of 36.80-44.23% obtained for cowpea/maize moimoi (Akusu & Kiin-Kabari, 2012).…”
Section: Proximate Compositioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Every child has the right to be born well, and to be cared and raised well. 2. Every child has the right to live with a family, who loves, cares and teaches good morals to him or her.…”
Section: Child Rights Act In Nigeriamentioning
confidence: 99%
“…Families should adopt and maintain good communication networks in the family as this will enable adolescents understand the need for conflict resolution through communication. 2. Family values must be maintained by the family, and inculcated in the children.…”
Section: Recommendationsmentioning
confidence: 99%